The Review on the European and the United States Healthcare Systems - Andrew S. Targowski (Public Health, 2025)
The paper investigates the main ideas and solutions of healthcare systems in leading countries such as Switzerland, the Neth-erlands, Denmark, Sweden, Austria, France based on the international ranking indexes such as the United Nations Human Development Index, Genuine Progress Indicator (GPI), Blumberg’s Global Health Index, World Health Organization (WHO), The Healthcare Access & Quality Index (HAQ), the European Health Consumer Index (EHCI). In conclusion, the health of society depends to a great extent on lifestyle and climate, where such countries as Spain and Italy have fewer sick people, and it results in a lower burden on healthcare. Unites States of America healthcare must compensate for lifestyle defects with intensive treatment and expensive medicines. This costs money and, what is worse, it doesn’t bring any noticeable progress. As evidenced by the dramas caused by the 2020 pandemic.